A Comparative Study of Primary Three Students’ Oral Interaction Achievement Learning Through Communication Games And Role Play at Burapa English Programme School of Thailand - Sachasiri, Manpreet; Eamoraphan, Suwattana (Scholar: Human Sciences, 2017)
This study focuses on primary 3 students’ oral interaction achievement at Burapa English Programme School of Thailand (BEST). Forty students participated in this study. The study used a two experimental group design where the sample was divided in two groups. Group A students learning through communication games and role play as a teaching approach, while group B students learning through role play and communication game as another teaching approach. The purpose of this study is to investigate if there is a significant difference of learning English through two different approaches. First approach is learning English through communication games and role play and the second approach is learning English through role play and communication games. The quantitative data acquired from the experimental groups gave the conclusion that, there was a significant difference in the students’ oral interaction achievement. The study concludes with recommendation for practice for teachers; they can implement different ways in teaching English as a foreign language for students to build up confidence in their English verbal skills. The study also gives recommendation for further research.